Satã-Griô: relatos dos caminhos e encruzilhadas na vida de um corpo negro-resistência - Rodrigues, Fernanda Brito (Universidade Federal de São Carlos, 2022)
The present research has as general objective to analyze the ways of survival and work of the subject João Francisco dos Santos, the Madame Satã during his life. Through documentary and bibliographic research, it is possible to seek the voice of Satan in the first person, so that he can tell us about his paths, supported by his interviews and his autobiography. From this path, the research questions arise: “How can a subject like João, black, ex-enslaved, living in the then federal capital, build his survival through work?” and “What possibilities can there be for a black, illiterate and marginalized body to tell their own story?”, from which arises the hypothesis of Satã-Griô, the teller of his own story. Satã, at the crossroads of life in the face of structural racism, gains space within his human condition in the search for dignity, and becomes a rogue, cook and artist. From the observation, deep and sensitive listening of this subject, we can see who the subject João was, and in what his story speaks to our history as a nation.
Satã-Griot: accounts of the paths and crossroads of the life of a black body-resistance
Keywords: Madame Satã; Malandragem Carioca; Oratura; Racismo Estrutural; Orature; Structural Racism; CIENCIAS HUMANAS